Dampak Pengumuman Covid-19 Terhadap Return Saham: Penelaahan Beberapa Sektor Industri - Leni Sari; Hariman Bone (Akuntabilitas, 2021)
This Research is an event study that examine abnormal return difference before and after first announcement of covid-19 case in Indonesia. This Study use daily closing price data to calculate returns. We use 30 days estimation period and 20 days window period. The data collection method is purposive sampling. There are 64 companies that meet the establish criteria. Wilcoxon signed rank test and paired sample t-test were used to examine the difference in abnormal return before and after the covid-19 first case announcement in Hotel, Restaurant & Tourism, Banking and telecommunication sector. This study found that there was no difference in abnormal returns before and after the announcement of the first Covid-19 case in Hotel, Restaurant & Tourism and Banking sector. Furthermore, this study found differences in abnormal return before and after the announcement of the first covid 19 case in telecommunication sector. How to Cite:Sari, L., & Bone, H. (2021). Dampak Pengumuman Covid-19 Terhadap Return Saham: Penelaahan Beberapa Sektor Industri. Akuntabilitas: Jurnal Ilmu Akuntansi, 14(2), 269-278.